Seismic Retrofit of an Existing RC Building With Isolation Devices Applied at Base - D'Amato, Michele; Laguardia, Raffele; Gigliotti, Rosario (Frontiers in Built Environment, 2020)
Nowadays, seismic retrofit through isolation strategy represents a consolidated technique of protection against design earthquakes. This technique is also widespread applied on existing structures, due to the fact that usually it does not require any interruption of the building use and occupants evacuation. If applicable, it rapidly allows of seismically retrofitting a building installing seismic devices with low horizontal stiffness between the structure and the foundation decoupling, in fact, the motion of the superstructure from the ground one. In this paper an application on an existing RC building of the seismic isolation is presented. The chosen building was built in the ‘90s only for vertical loads and realized without any detailing rule for structural ductility. The seismic retrofitting requirement stems from the fact that only recently, after the National seismic hazard maps update in 2003, the considered area has been upgraded to a medium-low seismic intensity zone, while at construction time no seismic classification was in existence by law. The case study peculiarity is that the seismic retrofitting has required in addition to seismic devices at the base with related interventions, also the application of a bracing system consisting of two elastic steel frames. This intervention is required for stiffening the superstructure and, therefore, for minimizing the higher vibration modes effects. The paper presents the main results obtained with a FEM model, implemented for simulating the initial and the design state when the interventions are considered. Finally, some results of non-linear dynamic time-history analyses are illustrated and commented for verifying superstructure elements and seismic devices.